Analisis Unsur Fisik dan Unsur Batin pada Puisi Pendosa, Doa, Aku Tidak Akan Berhenti Mencarimu, Kepada Tuhan Karya Heri Isnaini (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research discusses the meaning and religious message in four poems entitled "Sinner", "Prayer", "I Will Not Stop Looking for You", "To God" by Heri Isnaini. The purpose of this research is to find out how poets convey the spiritual connection between humans and God. The research was conducted using the Literature Study method. Poetry is analyzed based on themes, word meanings, and language use that reflects religious values. The results of the study show that the poems describe feelings of guilt, hope, love, and an effort to get closer to God. The language used is simple but full of meaning and symbols. The conclusion of this study is that poetry is a medium to convey love and search for God in a deep and honest way.